Correlation Between Cardiopulmonary Bypass Time (CPB Time) during Coronary Artery Bypass Graft on ICU Length of Stay - Andreas Rama Arkananta Nugraha; Danang Himawan Limanto; Philia Setiawan; Atika (Universitas Airlangga, 2024)
Highlight: 1. CHD remains one of the most threatening CVD in Indonesia. Studies discussing CHD will contribute in future studies for cardiologists to assert better options for treatment. - Abstract Background: Coronary heart disease (CHD) is one of the deadliest diseases in Indonesia. Coronary artery bypass graft using cardiopulmonary bypass (CPB) is an integral measure in its treatment. The objective of this study is to identify the correlation of CPB Time and Length of Stay (LOS) in the Intensive Care Unit (ICU) in Dr.Soetomo General Academic Hospital, Surabaya. Material and Methods: This study was conducted using observational and analytic methods. The population are coronary heart disease patients who underwent coronary artery bypass graft. A total sampling method was used from the medical records of Dr. Soetomo General Academic Hospital, Surabaya from October 2021 until September 2022. The research variables are: CPB time and ICU LOS. The relationship between CPB and ICU LOS was analyzed using the Spearman correlation test and logistic regression as well Mann-Whitney test using Microsoft Excel and SPSS version 25. Results: From the results of the correlation test, there is no correlation between CPB Time and ICU LOS with a correlation coefficient of r=0212, there is no significant difference between CPB â‰¤180 minutes and CPB >180 minutes on ICU LOS p=0.123. From the overall sample, the average age was 62.24+7.765 years, with the majority of the sample were male 87.3%. Conclusion: There is no correlation between the CPB Time and ICU LOS in patients after coronary artery bypass graft at RSUD Dr. Soetomo.